The frequency of BRCA1 founder mutation c.5266dupC (5382insC) in breast cancer patients from Ukraine. Issue 1 (December 2015) - Gorodetska, Ielizaveta; Serga, Svitlana; Levkovich, Natalia; Lahuta, Tetiana; Ostapchenko, Ludmila; Demydov, Serhyi; Anikusko, Nikolay; Cheshuk, Valeriy; Smolanka, Ivan; Sklyar, Svitlana; Polenkov, Serhyi; Boichenko, Oleksander; et al.
Abstract Germ-line mutations in several genes, such asBRCA1 andBRCA2, are known to increase the risk of breast cancer. These heritable mutations are unequally represented among populations with different ethnic background due to founder effects and thereby contribute to differences in breast cancer rates in different populations. TheBRCA1 mutation c.5266dupC (also known as 5382insC or 5385insC) was detected in a sample of 193 breast cancer patients in Ukraine by multiplex mutagenically separated PCR using published specific primers. NineBRCA1 mutations 5382insC were detected (4.7 %). The difference in age of diagnosis (35 years in 5382insC carriers versus 45 years in non-carriers) we observed is consistent with other reports indicating that the 5382insC mutation is a factor of genetic predisposition to breast cancer, which is consistent with reports from other countries.